2022
DOI: 10.1021/acs.est.2c00581
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Polychlorinated Biphenyls and Their Hydroxylated Metabolites in Postmortem Human Brain Samples: Age and Brain Region Differences

Abstract: Exposure to polychlorinated biphenyls (PCBs) and their hydroxylated metabolites (OH-PCBs) has been implicated in neurodevelopmental disorders. However, the distribution of PCBs and OH-PCBs in the human brain has not been characterized. This study investigated the age-, sex-, and brain region-specific distribution of all 209 PCBs using gaschromatography–tandem mass spectrometry (GC–MS/MS) in neonatal ( N = 7) and adult ( N = 7) postmortem brain samples. OH-PCB analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 100 publications
0
45
1
Order By: Relevance
“…Eighty-one single or co-eluting PCB congeners were detected in zero samples; 76 in 1-10% of samples; 5 in 11-20% of samples; 7 in 21-50% of samples; and 4 in ≥50% of samples (Supplemental Table S1). These detection frequencies are lower than those in postmortem human brain using similar methods (Li, Hefti, et al, 2022). In both studies, highly chlorinated PCBs were more likely to be detected than lower chlorinated PCBs, despite the decreased response of the instrument as the degree of chlorination increases.…”
Section: Highly Chlorinated Pcb Congeners Are Most Frequently Detecte...mentioning
confidence: 60%
See 4 more Smart Citations
“…Eighty-one single or co-eluting PCB congeners were detected in zero samples; 76 in 1-10% of samples; 5 in 11-20% of samples; 7 in 21-50% of samples; and 4 in ≥50% of samples (Supplemental Table S1). These detection frequencies are lower than those in postmortem human brain using similar methods (Li, Hefti, et al, 2022). In both studies, highly chlorinated PCBs were more likely to be detected than lower chlorinated PCBs, despite the decreased response of the instrument as the degree of chlorination increases.…”
Section: Highly Chlorinated Pcb Congeners Are Most Frequently Detecte...mentioning
confidence: 60%
“…The four PCB congeners/congener pairs that were detected in ≥50% (n=52) of samples were selected for further analysis due to the increased robustness of statistical methods when censored data points represent less than half the data: PCBs 153s + 168, 170, 180 + 193, and 187. These PCB congeners were also detected in ≥50% of postmortem brain samples (Li, Hefti, et al, 2022) and found at high concentrations in maternal blood plasma, cord blood plasma, breast milk (Guvenius et al, 2003), and placenta (Naqvi et al, 2018). No PCB congeners were detected in fewer than 50% of all samples but in greater than 50% of one of the ASD diagnostic groups (ASD/non-TD/TD), indicating that we did not miss a congener that may discriminate between diagnostic groups.…”
Section: Highly Chlorinated Pcb Congeners Are Most Frequently Detecte...mentioning
confidence: 86%
See 3 more Smart Citations